2006
DOI: 10.1002/rcm.2501
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of fatty acid ester metabolites of spirolide toxins in mussels from Norway using liquid chromatography/tandem mass spectrometry

Abstract: Cultured mussels sampled in the spring of 2002 and 2003 from Skjer, a location in the Sognefjord, Norway, tested positive in the mouse bioassay for lipophilic toxins. In a previous report, it was established that a number of spirolides, cyclic imine toxins produced by the phytoplankton Alexandrium ostenfeldii, were present in the mussels and were responsible for the observed toxicity. The main toxin proved to be a new compound named 20-methyl spirolide G. In subsequent studies, a delayed onset of spirolide-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 14 publications
5
54
0
Order By: Relevance
“…They were not detected in a survey of mussel samples from Norway, 18 despite the occurrence of esters of other toxin groups in mussels harvested in similar locations. 23,26 No acyl esters of 6 were observed following base hydrolysis of contaminated oysters (Crassostrea gigas) from South Australia. 6 A recent study looking at the occurrence of benthic toxins from harbors in New Zealand found significant quantities of pinnatoxins and okadaic acid in a variety of marine organisms.…”
Section: Direct Determination Of Pinnatoxin Esters By Lc-msmentioning
confidence: 99%
See 1 more Smart Citation
“…They were not detected in a survey of mussel samples from Norway, 18 despite the occurrence of esters of other toxin groups in mussels harvested in similar locations. 23,26 No acyl esters of 6 were observed following base hydrolysis of contaminated oysters (Crassostrea gigas) from South Australia. 6 A recent study looking at the occurrence of benthic toxins from harbors in New Zealand found significant quantities of pinnatoxins and okadaic acid in a variety of marine organisms.…”
Section: Direct Determination Of Pinnatoxin Esters By Lc-msmentioning
confidence: 99%
“…The presence of 7-O-acyl derivates of okadaic acid and dinophysistoxins has been well documented, 20−23 and similar acyl esters of pectenotoxins, 24 brevetoxins, 25 and spirolides 26 have been reported. Because pinnatoxins also contain hydroxyl groups that could be acylated, it seems possible that similar metabolites of these compounds would occur.…”
Section: ■ Introductionmentioning
confidence: 99%
“…All known spirolides have so far been linked to two producing organisms, dinoflagellate Alexandrium ostenfeldii 14,17,19,31,32,33,34,40 and Alexandrium peruvianum . 13,35,36,37 A. ostenfeldii is a gonyaulacoid 38 dinoflagellate that has long been considered confined to Northern cold-temperature oceanic waters (Figure 3D).…”
Section: Isolation and Algal Originmentioning
confidence: 99%
“…Operating the software programme ToxID 2.1.2 (Thermo Fisher Scientific, San José, USA), the full-scan data of three culture extracts were efficiently screened. To this end, a ToxID database from Gerssen et al [15] was modified by adding new compounds and molecular formulas of 98 relevant toxins [24,[50][51][52][53][54][55][56][57][58][59][60][61][62], see Table S1 …”
Section: Algal Toxin Profilementioning
confidence: 99%